2021
DOI: 10.1186/s12879-021-06156-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of anti-SARS-CoV-2 IgG antibodies post-COVID-19 in a Brazilian Amazon population

Abstract: Background In this study, the prevalence and persistence of anti-SARS-CoV-2 (severe acute respiratory syndrome-coronavirus) IgG was evaluated in volunteers 90 days after COVID-19 (coronavirus disease 2019) diagnosis by correlating response dynamics with clinical conditions, epidemiological characteristics, and disease severity. Methods The study recruited 200 volunteers aged 18 years or older of both sexes diagnosed with COVID-19. Of the 200 volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…In our study, sensitivity of the test in the subset of patients >60 days from symptom onset was 88%, indicating that IgG responses can be tracked in individuals during the first two months. This coincides with previous reports of a median half-life of antibodies detected by Abbott of 86 days [ 35 ], and a decay in seropositivity after 90 days reported in a Brazilian population evaluated with this test [ 39 ]. These aspects should be considered when analyzing and interpreting serosurveys conducted globally with the Abbott assay, since the true cumulative number of SARS-CoV-2 infections may be underestimated.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, sensitivity of the test in the subset of patients >60 days from symptom onset was 88%, indicating that IgG responses can be tracked in individuals during the first two months. This coincides with previous reports of a median half-life of antibodies detected by Abbott of 86 days [ 35 ], and a decay in seropositivity after 90 days reported in a Brazilian population evaluated with this test [ 39 ]. These aspects should be considered when analyzing and interpreting serosurveys conducted globally with the Abbott assay, since the true cumulative number of SARS-CoV-2 infections may be underestimated.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in a longitudinal study, Peghin et al [10] observed IgM seroconversion in 90% of patients and its decline within 4 months. In our previous follow-up study, we reported a high frequency of loss of anti-SARS-CoV-2 IgG antibodies within 3 months after COVID-19 diagnosis in the Brazilian Amazon, but without information about IgM [11].…”
Section: Introductionmentioning
confidence: 87%
“…Our collective understanding of the required magnitude and composition of a protective immune response against SARS-CoV-2 continues to develop. Early investigations of infection-induced responses for diagnostic purposes included evaluation of IgA, IgM and IgG humoral immunity ( Ma et al, 2020 ; Bichara et al, 2021 ; Maeda et al, 2021 ) and many commercial kits have been developed for these endpoints. SARS-CoV-2 specific IgA seems to be a high performing early diagnostic endpoint ( Ma et al, 2020 ; Sterlin et al, 2021 ), while the kinetics of post-infection IgM and IgG better reflect peak and waning immunity in convalescent cohorts ( Bichara et al, 2021 ; Duysburgh et al, 2021 ; De Greef et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early investigations of infection-induced responses for diagnostic purposes included evaluation of IgA, IgM and IgG humoral immunity ( Ma et al, 2020 ; Bichara et al, 2021 ; Maeda et al, 2021 ) and many commercial kits have been developed for these endpoints. SARS-CoV-2 specific IgA seems to be a high performing early diagnostic endpoint ( Ma et al, 2020 ; Sterlin et al, 2021 ), while the kinetics of post-infection IgM and IgG better reflect peak and waning immunity in convalescent cohorts ( Bichara et al, 2021 ; Duysburgh et al, 2021 ; De Greef et al, 2021 ). Interestingly, some studies have observed pro-inflammatory IgG subsets (IgG1 and IgG3) trend higher with severity of clinical COVID-19 disease while others (IgG2 and IgG4) are rarely detected ( Yates et al, 2021 ; Luo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%